Efficacy of Various Approaches to Treatment of Patients with Isoniazid Resistant Pulmonary Tuberculosis - I. A. Burmistrova; E. V. Vaniev; A. G. Samoylova; O. V. Lovacheva; I. A. Vasilyeva (Туберкулез и болезни лёгких, 2023)
The objective: to evaluate the efficacy of chemotherapy regimens for isoniazid resistant pulmonary tuberculosis (Hr-TB): short-course regimen consisting of 4 components (non-injection) and the regimen consisting of 5 components (standard regimen).Subjects and Methods. Medical records of 292 pulmonary tuberculosis patients with resistance to isoniazid were retrospectively studied. In 89 patients (Group A), the regimen containing rifampicin, pyrazinamide, ethambutol, and levofloxacin was used – a 4-component non-injection regimen (180±20 doses). In 203 patients (Group B), the regimen containing rifampicin, pyrazinamide, ethambutol, levofloxacin, and amikacin/kanamycin was used - a 5-component standard regimen (270 doses).Results. The efficacy of treatment of isoniazid resistant pulmonary tuberculosis was similar, while a short-term 4-component (non-injection) regimen is 4.5 times less expensive versus the standard 5-component regimen. Treatment success made 88.8% and 88.2% respectively, p>0.05.